2010
DOI: 10.1128/jcm.01789-09
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Strains ofYersinia enterocoliticaIsolated from Domestic Dogs (Canis familiaris) Belonging to Farmers Are of the Same Subtype as PathogenicY. enterocoliticaStrains Isolated from Humans and May Be a Source of Human Infection in Jiangsu Province, China

Abstract: We isolated 326 Yersinia enterocolitica strains from 5,919 specimens from patients with diarrhea at outpatient clinics, livestock, poultry, wild animals, insect vectors, food, and the environment in the cities of Nantong and Xuzhou in Jiangsu Province, China, from 2004 to 2008. The results showed that the 12 pathogenic strains were of the O:3 serotype. Six strains were isolated from domestic dogs (Canis familiaris) belonging to farmers and were found to be the primary carriers of pathogenic Y. enterocolitica s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 27 publications
(25 reference statements)
4
49
0
3
Order By: Relevance
“…enterocolitica is regarded as a significant food-borne pathogen (1,2). Besides food from animal sources, especially pork (13,26), companion animals have been implicated as a potential source for human Yersinia infections (4,7,14,16,23,25,43). Strains isolated from dogs in particular share common genotypes with pathogenic strains isolated from humans (7,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enterocolitica is regarded as a significant food-borne pathogen (1,2). Besides food from animal sources, especially pork (13,26), companion animals have been implicated as a potential source for human Yersinia infections (4,7,14,16,23,25,43). Strains isolated from dogs in particular share common genotypes with pathogenic strains isolated from humans (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent Chinese studies placed greater relevance on companion animals, especially dogs, as primary sources of infection in humans, although dogs consumed as food were an additional source of infection, which is not a factor that needs to be considered in Europe (24,25). It was shown that some pathogenic Y. enterocolitica strains isolated from ill humans and dogs had the same subtype as well as the same pattern by pulsedfield gel electrophoresis (25). In previous case-control studies, contact with companion animals was shown to be a confirmed risk factor for human yersiniosis (24,26).…”
mentioning
confidence: 99%
“…The strain 105.5R(r) was recovered in 1996 from a patient in the People's Hospital of Shenyang in Jilin City, Liaoning Province, China. Characterization of this strain has been described previously (43).…”
Section: Methodsmentioning
confidence: 99%
“…Y. enterocolitica has established a broad base of animal reservoirs; however, colonization in swine presents the most robust capacity for transmission to humans (22,32), and dogs have been implicated as a potentially significant source in rural families (43). Human infection is primarily localized to the gastrointestinal tract, where a wide range of syndromes can emerge in response to the bacteria's presence, including enteritis, enterocolitis, mesenteric lymphadenitis, and terminal ileitis (6).…”
mentioning
confidence: 99%
“…Y. pseudotuberculosis and Y. enterocolitica are zoonotic food-borne pathogens that spread through the fecal-oral route; they have a broad host range, infecting animals, including swine, dogs, rodents, birds, and wild animals (3,4). Many studies show that swine and dogs are the most common sources of Y. enterocolitica infections in humans (5,6). These enteropathogens cause human enteric diseases, both sporadically and in epidemics worldwide.…”
mentioning
confidence: 99%